Robust H∞ output-feedback control for path following of autonomous ground vehicles. (March 2016) - Hu, Chuan; Jing, Hui; Wang, Rongrong; Yan, Fengjun; Chadli, Mohammed
Abstract: This paper presents a robust H ∞ output-feedback control strategy for the path following of autonomous ground vehicles (AGVs). Considering the vehicle lateral velocity is usually hard to measure with low cost sensor, a robust H ∞ static output-feedback controller based on the mixed genetic algorithms (GA)/linear matrix inequality (LMI) approach is proposed to realize the path following without the information of the lateral velocity. The proposed controller is robust to the parametric uncertainties and external disturbances, with the parameters including the tire cornering stiffness, vehicle longitudinal velocity, yaw rate and road curvature. Simulation results based on CarSim–Simulink joint platform using a high-fidelity and full-car model have verified the effectiveness of the proposed control approach. Abstract : Highlights: Output-feedback control of autonomous vehicles without the information of the lateral velocity. The proposed controller is robust to the parametric uncertainties and external disturbances. Vehicle stability is simultaneously enhanced by controlling the vehicle slip angle.